4 th International Health Economics & Outcomes Research Conference-2025 - Organized by International Society for Pharmacoeconomics; Outcomes Research (ISPOR) India Andhra Pradesh Regional Chapter (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Raghavendra Institute of Pharmaceutical Education and Research (RIPER)-Autonomous, Chiyyedu Post, Anantapur, India 25 & 26 April, 2025 Andhra Pradesh, India